Colombian sovereignty on the 82nd meridian. The role of the International Court of Justice in the territorial delimitation process between Colombia and Nicaragua - Henao Cardenas, Juan Camilo; Londoño Martínez, Mónica; Vasco del Río, Claudia Andrea (Revista Colombiana de Ciencias Sociales, 2026)
The paper analyzes the problems between Colombia and Nicaragua regarding their border delimitation and the ruling of the International Court of Justice (ICJ), a ruling that questioned the acts of sovereignty exercised by Colombia in the 82nd Meridian and the loss of sea in the archipelago of San Andres, Santa Catalina and Providencia in favor of Nicaragua. This paper is documentary review research, qualitative in nature, whose main methodology is the analysis of a single case and the position of different authors regarding the Bárcenas-Esguerra treaty. The strategy was based on the collection of information, supported by documents, where a detailed tracking of texts, articles, books and columns that dealt with the research topic was carried out, by means of the elaboration of a comparative matrix of texts. The results show that the authors coincide in stating that the Court did not consider several aspects of international law that revolve around sovereignty, international relations, the law of the sea, the Principle of Pacta Sunt Servanda and territorial law.